SPEED OF ADJUSTMENT TOWARDS TARGET CAPITAL STRUCTURE IN INDONESIAN PROPERTY AND REAL ESTATE COMPANIES - Nurlaila Badrina (19015081), Nadia
This study aims to explains the empirical evidence of the determinants of capital structure in both static and dynamic model in property and real estate industry in Indonesia during the period of 2008-2017, as well as the speed of adjustment, whether the adjustment is done actively by corporate action or passively by using retained earning. This study used multiple regression method to test the determinants of capital structure; growth opportunity, size of firm, dividend payout, profitability, tangibility, liquidity and loan to value ratio. The dynamic model used the lagged version of the static variable plus lagged leverage in active adjustment and passive adjustment. This research proved that growth opportunity, size of firm, profitability, and tangibility are significant towards leverage at 5% significance level and liquidity is significant at 10% significance level. The dividend payout and loan to value ratio proved to be not significant towards capital structure in property and real estate companies. The dynamic model proved that the property and real estate industry has a target capital structure. On the active adjustment model, the active lagged leverage and lagged size of firm are significant at 5% significance level and lagged growth opportunity is significant at 10% significance level towards the target capital structure. Lagged dividend payout, lagged profitability, lagged tangibility, lagged liquidity, and lagged loan to value ratio are not significant to the target capital structure. The passive adjustment model shows similar result to active adjustment model but lagged growth opportunity is not significant to target capital structure. Property and real estate industry speed of adjustment towards target leverage is 24.54% and 26.71% each year for active adjustment and passive adjustment respectively. This study found that in property and real estate, firms tend to adjust their capital structure passively.